2023
DOI: 10.1039/d3ob00424d
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in the accessibility, synthetic utility, and biological applications of aziridines

Abstract: Compounds featuring aziridine moieties are widely known and extensively used in literature. Due to their great potential from a synthetic and pharmacological point of view, many researchers focus their efforts...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 142 publications
(187 reference statements)
0
11
0
Order By: Relevance
“…Finally, we expanded the developed method for the synthesis of oxazolidinones from aziridines. After testing several catalysts reported in the literature (Table 4), 30 we identified the Lewis acidic tetrabromoferrate ionic liquid formed from tetrabutylammonium bromide (TBAB) and FeBr 3 as the most suitable catalyst for continuous-flow formation of oxazolidinones (entry 8). 31 The reaction was carried out at room temperature, and the back-pressure regulator was set to 5 bar.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Finally, we expanded the developed method for the synthesis of oxazolidinones from aziridines. After testing several catalysts reported in the literature (Table 4), 30 we identified the Lewis acidic tetrabromoferrate ionic liquid formed from tetrabutylammonium bromide (TBAB) and FeBr 3 as the most suitable catalyst for continuous-flow formation of oxazolidinones (entry 8). 31 The reaction was carried out at room temperature, and the back-pressure regulator was set to 5 bar.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…We have recently shown that the cheap metal cobalt and NFSI constitute a competent catalytic system in the highly regioselective vicinal aminofluorination 12 and Markovnikov/anti-Markovnikov hydroamination of alkenes. 13 In continuance of our research interest in redox cobalt catalysis, 15 we find that this catalytic system effectively promotes the nucleophilic amination of aziridines 16 and furnishes the ring-opened 1,2-diamine scaffolds. 17 Meanwhile, the same strain-release strategy is also applicable to the analogous nucleophilic amination of azetidines 18 to construct 1,3-diamines.…”
Section: Introductionmentioning
confidence: 94%
“…The recognition of heterocyclic fused rings has grown significantly, attributed to the improved pharmacological properties they offer, especially in nitrogen-containing architectures ( Dank and Ielo, 2023 ). In particular, pyrrolidine-fused coumarins have been considered attractive targets in drug design, thanks to the biochemical relevance of both combined scaffolds ( Ren et al, 2021 ).…”
Section: Synthesesmentioning
confidence: 99%